First correct answer= brainlist
![First correct answer brainlist class=](https://us-static.z-dn.net/files/d6b/f9d6fc5cd2b49b85ed4a3b02a0829df3.png)
Answer:
[tex]-a^2+ab[/tex]
Step-by-step explanation:
So the sentence can be written like this:
[tex]((a^2-b^2)+(a^2+ab+3b^2))-((a^2-2ab+b^2)+(2a^2+2ab+b^2))[/tex]
Now you can combine like terms in the first part of the equation and the second part:
[tex]((a^2+a^2)+ab+(-b^2+3b^2))-((a^2+2a^2)+(-2ab+2ab)+(b^2+b^2))[/tex]
Which leaves you with:
[tex](2a^2+ab+2b^2)-(3a^2+2b^2)[/tex]
Now distribute the negative to the second part of the equation:
[tex]2a^2 + ab + 2b^2-3a^2-2b^2[/tex]
Combine like terms again:
[tex](2a^2-3a^2)+ab+(2b^2-2b^2)[/tex]
Which becomes:
[tex]-a^2+ab[/tex]
Answer:
- a² + ab
Step-by-step explanation:
summing the first 2 expressions
a² - 2ab + b² + 2a² + 2ab + b² ← collect like terms
= 3a² + 2b² → (1)
summing the next 2 expressions
a² - b² + a² + ab + 3b² ← collect like terms
= 2a² + ab + 2b² → (2)
Subtracting (1) from (2)
2a² + ab + 2b² - (3a² + 2b²) ← distribute parenthesis by - 1
= 2a² + ab + 2b² - 3a² - 2b² ← collect like terms
= - a² + ab